STUDY ON THERMAL DEFORMATIONS OF THE PRIMARY SEALING OF FRONT SEALING - Mihaela ISTRATE; Monica BÂLDEA; Ancuța BĂLTEANU; Jan Cristian GRIGORE (Fiabilitate şi Durabilitate)
The thermal phenomena appear at the level of the film within the primary sealing interstitium. An important temperature gradient is performed in the stator and in the rotor, which produces thermoelastic deformations. These deformations are of the order of film width and affect essentially the interstitium geometry. According to the temperature increase direction the repartition in the friction ring is different. The farthest areas from the temperature drops or the nearest to the heat sources will have he highest temperature. These dilate more that the rest of the areas and modify the interstitium form. From the calculation relations it comes out that deformations depend also on certain operating conditions, which can be modified through time (pressure, temperature), the sealing efficiency being thus different in time.